L’amministrazione delle aziende confiscate alla criminalità organizzata. La proposta di un framework di studio e un’analisi esplorativa dei decreti di destinazione - La Rosa, Fabio; Paternostro, Sergio (Piccola Impresa / Small Business, 2015)
This work addresses the issue of the administration of seized and confiscated firms against organised crime. The first part develops a conceptual framework that aims to highlight both the conditions prior to seizure measure and the variables of the seizure and confiscation phase, which may affect the recovery path of legality. The second part of the work is devoted to a first exploratory survey of the phenomenon starting from the content analysis of the “destination decrees” publicly accessible. The aim is to verify the quantity and quality of information available under the most important measure that decides the chance of the confiscated firm. Finally, we interpret the content of the “destination decrees” in the light of the proposed framework. What emerges is a very fragmented picture of information, not yet useful to ensure a knowledge base able to support the continuation of the business